Passive Communication and the Silent Treatment in Social Relations of Adolescents in Cirebon City - Alfilo Gian Rachmat Hudaya; Farhan Alfadhil Suhendar; Farida Nurfalah (Journal of World Science, 2025)
This study examines the phenomenon of the silent treatment as passive communication in adolescent social relationships in Cirebon City. The silent treatment is defined as the deliberate refusal to engage in verbal communication, often employed as a response to conflict. The aim of this research is to analyze the motivations, emotional responses, and relational dynamics associated with silent treatment, as well as to explore the perceptions of both the initiators and recipients of this behavior. This study utilized a qualitative case study approach, focusing on adolescents aged 16–20 in Cirebon with experience giving or receiving silent treatment. Data were collected through in-depth interviews and analyzed using observation, documentation, and literature review techniques. The Johari Window theory applied to examine the dynamics of self-disclosure within the context of silent treatment. The findings suggest that the silent treatment is not an effective method of conflict resolution; rather, its repeated use can deteriorate interpersonal relationships. Besides, the study also indicates that the silent treatment serves as a conflict-avoidance tactic, yet it frequently elicits negative emotional responses, including feelings of devaluation, frustration, and relational deterioration. The study further demonstrates the value of self-disclosure in reducing instances of miscommunication and promoting more effective interpersonal relations. This study recommends education about healthy communication and emotional management for adolescents to prevent the use of silent treatment in social relationships.